Implication of Nonalcoholic Fatty Liver Disease, Metabolic Syndrome, and Subclinical Inflammation on Mild Renal Insufficiency - Ga Eun Nam; Soon Young Hwang; Hye Soo Chung; Ju Hee Choi; Hyun Jung Lee; Nam Hoon Kim; Hye Jin Yoo; Ji-A Seo; Sin Gon Kim; Nan Hee Kim; Sei Hyun Baik; Kyung Mook Choi (International Journal of Endocrinology)
Background. Limited information exists about the impact of nonalcoholic fatty liver disease (NAFLD) on mild renal insufficiency. We compared the relative influence of NAFLD, metabolic syndrome (MetS), and subclinical inflammation, alone or in combination, on mild renal insufficiency. Methods. This study included 1174 Korean adults. NAFLD was diagnosed using ultrasonography. Mild renal insufficiency was defined as an estimated glomerular filtration rate (eGFR) ≥ 60 and <90 mL/min/1.73 m2. Results. In partial correlation analysis, several components of MetS and liver aminotransferase levels, but not high-sensitivity C-reactive protein (hsCRP), were associated with eGFR. Multivariate logistic regression analysis demonstrated the independent association of NAFLD (P=0.034) and MetS (P=0.018) with mild renal insufficiency, but not elevated hsCRP (P=0.885). Furthermore, NAFLD without the MetS group (odds ratio (95% confidence interval) = 1.56 (1.05–2.34)) or MetS without the NAFLD group (1.82 (1.11–3.00)) was associated with mild renal insufficiency after adjusting for confounding variables. However, individuals with high hsCRP showed no relationship with mild renal insufficiency, irrespective of the existence of NAFLD. Conclusions. This study demonstrated that NAFLD and MetS are independently associated with mild renal insufficiency, whereas subclinical inflammation did not affect the risk for mild renal insufficiency in Korean adults.